Cultural osteology - Weiss, Pedro (1958)
Pottery is the royal road of archaeologists to explore the pre-history. The exceptional conditions of this material in Peru excuse to be shelved others, also in Peru offer endless possibilities. The name archaeologists have emphasized issues of Osteology, at least in what concerns the trepanation and deformations, seems sufficient guarantee of merit. Uhle, Tello and Kroeber, used data from the Osteology and are dedicated to discussing the need to take into account the skulls in the diagnosis of cultures paragraphs.